Bibliometric Analysis of Urban and Rural Economic Inequality - Loso Judijanto; Iwan Harsono; Ilham Akbar Bunyamin (Westscience Press, 2024)
This bibliometric study provides a comprehensive analysis of the scholarly landscape surrounding research on economic inequality, utilizing VOSviewer to visualize the thematic clusterization, temporal trends, emerging research opportunities, and collaborative networks in the field. The analysis begins with the identification of key thematic areas, revealing a complex interplay between income inequality, urban-rural disparities, and their socioeconomic impacts. A temporal examination traces the evolution of research themes from foundational studies focusing on regional disparities to more comprehensive explorations of socioeconomic outcomes. Emerging research opportunities are identified in less explored areas, suggesting potential for significant contributions through novel investigations. Furthermore, the study delves into collaborative networks, highlighting the pivotal roles of central researchers and the impact of academic partnerships. This study not only maps out the current academic terrain but also proposes strategic directions for future research, aiming to enhance the understanding and resolution of economic inequalities.